Energy and economic growth why we need a new pathway to prosperity - Foxon, Tim 1967- (Routledge studies in energy transitions., 2018)
"Energy and Economic Growth thus examines the links between three issues: history of energy sources, technologies and uses; ecological challenges associated with the current dominant economic growth paradigm; and the future low carbon energy transition to mitigate human-induced climate change. Providing a historical understanding of the relevant connections between physical, social and economic changes, the book enables the reader to better understand the connection between their own energy use and global economic and environmental systems, and to be able to ask the right questions of our political and business leaders."--Provided by publisher.